EFEKTIVITAS MEDIA STATAK DIGITAL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SDN 02 SELAT PANJANG - Susilawati, Susilawati; Erda, Gustriza; Hasbiyati, Ihda; M, Musraini; Agustiarni, Efni; Bustami, Haposan Sirait; Rahman, Fadhila (Unri Conference Series: Community Engagement, 2025)
Mathematics learning in elementary schools is often considered abstract, difficult to understand, and uninteresting for students. On the other hand, traditional games such as Statak have the potential to be a fun, contextual learning medium. Digitizing this traditional game is seen as a solution to increase student interest and learning outcomes. This study aims to determine the effectiveness of digital Statak media in improving mathematics learning outcomes of fourth-sixth grade students at SDN 02 Selat Panjang. This study used a quasi-experimental approach with a one-group pretest-posttest design. The subjects were 26 fourth-sixth grade students. The instruments used consisted of a mathematics learning achievement test and a student response questionnaire. Data were analyzed using paired t-tests and descriptive analysis. The average pretest score was 77.5, while the average posttest score increased to 87. The t-test results showed a significant difference (p < 0.05) between the pretest and posttest scores. Digital Statak media has proven effective in improving mathematics learning outcomes for students at SDN 02 Selat Panjang. Furthermore, this media fosters learning motivation and plays a role in preserving local culture through the digitization of traditional games.